Análise da relação entre os fatores interno e externo e o desempenho acadêmico dos estudantes do curso de Engenharia da Computação da UEFS - Cardoso, Naan Silva (2019)
Academic performance, with respect to the student concept (i.e. grades, evaluation, approval/disapproval), has been one of the challenges that the Brazilian educational system has been facing in recent years. Some indicators show that the retention and dropout rates are high in the Computing courses. In this research, we sought to analyze the hypothesis that there is a relationship between internal (participation) and external (use of Social Media) factors and student academic performance. For this purpose, data collected from the smartphones of the subjects of this research and of the observation technique within the classroom were analyzed in order to confirm or refute such hypothesis. Data mining techniques such as correlation analysis are used to identify relationship between variables. The research was carried out with the students from Algorithms and Programming I, Algorithms and Programming II and two Data Structure classes T01 and T02, in the Computer Engineering course at the State University of Feira de Santana - UEFS. The results of the study indicate that for the internal factor, no statistically significant result was obtained to confirm the hypothesis that there is a relationship between student participation in classes and academic performance. For the external factor, the sample data points to a strong positive relationship between the use of Facebook in the performance and a significant negative relation between the use of Instagram, confirming the hypothesis that there is a relation between the external factor (Social Media) and the academic performance.